A continuous and multi valued system as molecular answer for data processing and data storage - Stockinger, Skrollan Carina; Trapp, Oliver (Chemical science, 2014)
A molecular logic system with a quaternary basis as well as a continuous system as an alternative related to logic concepts were made accessible. Both systems are based on a mixture of benzonitrile oxide, iron(III) chloride and either zinc or sodium thiocyanate, analysable by photography and subsequent RGB value analysis with a common image processing software. The quaternary logic system increases the possible amount of data processing by raising the arithmetic basis whereas the continuous system could extend the world of multi valued logic to real floating point operations with unprecedented precision. Additionally both systems are long-term stable and could for example be used as a high potential storage medium with a high data processing density.